Strategi Pembelajaran Tahfiz Al-Qur’an Di Mas Miftahussalam Medan - Dheria Rahima; Nanda Rahayu Agustia; Tumiran Tumiran (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study analyzes Al-Qur’an tahfiz learning strategies to enhance memorization quality at MAS Miftahussalam Medan. Employing a qualitative case study design, data were collected through interviews, observations, and documentation. The findings identify three core strategies: (1) optimizing morning